The diagnosis and management of mucopolysaccharidosis type II - Shao-Jia Mao; Qing-Qing Chen; Yang-Li Dai; Guan-Ping Dong; Chao-Chun Zou (BMC, 2024)
Abstract Mucopolysaccharidosis type II (MPS II) is a rare X-linked recessive inherited lysosomal storage disease. With pathogenic variants of the IDS gene, the activity of iduronate-2-sulfatase (IDS) is reduced or lost, causing the inability to degrade glycosaminoglycans (GAGs) in cells and influencing cell function, eventually resulting in multisystemic manifestations, such as a coarse face, dysostosis multiplex, recurrent respiratory tract infections, and hernias. Diagnosing MPS II requires a combination of clinical manifestations, imaging examinations, urinary GAGs screening, enzyme activity, and genetic testing. Currently, symptomatic treatment is the main therapeutic approach. Owing to economic and drug availability issues, only a minority of patients opt for enzyme replacement therapy or hematopoietic stem cell transplantation. The limited awareness of the disease, the lack of widespread detection technology, and uneven economic development contribute to the high rates of misdiagnosis and missed diagnosis in China.